2017
DOI: 10.1002/eji.201646760
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II alleles associated with Th1 rather than Th17 type immunity drive the onset of early arthritis in a rat model of rheumatoid arthritis

Abstract: Polymorphisms in the MHC class II (MHCII) genes are strongly associated with rheumatoid arthritis, supporting the importance of autoreactive T helper (Th) cells for the development of this disease. Here, we used pristane-induced arthritis (PIA), induced by the non-antigenic hydrocarbon pristane, to study the impact of different MHCII alleles on T-cell activation and differentiation. In MHCII-congenic rats with disease-promoting MHCII alleles, pristane primarily induced activation of Th1 cells, whereas activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…Pristane is a natural saturated terpenoid alkane, and known to induce autoimmune diseases in rodents for researching the pathogenesis of rheumatoid arthritis and lupus [ 7 , 8 ]. PIA is a T-cell-driven arthritis model, which is not dependent on the administration of exogenous antigens [ 9 , 10 ].Thus, PIA is very suitable for studying the role of cytokines in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Pristane is a natural saturated terpenoid alkane, and known to induce autoimmune diseases in rodents for researching the pathogenesis of rheumatoid arthritis and lupus [ 7 , 8 ]. PIA is a T-cell-driven arthritis model, which is not dependent on the administration of exogenous antigens [ 9 , 10 ].Thus, PIA is very suitable for studying the role of cytokines in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR analyses revealed that CD4 + T cells from the spleen of pristane-injected rats expressed lower levels of Th17associated cytokines than CD4 + T cells from dLNs, suggesting a difference in the proportion of Th17 cells (or in the relative expression of Il17 and Il22 transcripts) between the two organs. Therefore, given the importance of IL-17 in PIA [24], it is possible that spleen-, in contrast to LN-, derived T cells lack the properties necessary to sustain a chronic immune response. Moreover, as shown by Catron et al, tissue-draining LNs continue to be seeded by antigen-specific late-arriving T cells, which are enriched in central-memory cells, in the first several weeks after the primary immune response is over [40].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-mouse IL-17A antibody (clone 17F3; mouse IgG1) and isotype control antibody (clone MOPC-21) were obtained from Bio X Cell (West Lebanon, NH, USA). Crossreactivity to rat IL-17 has been evaluated previously [24].…”
Section: Antibodies and Immunosuppressive Reagentsmentioning
confidence: 99%
See 2 more Smart Citations